EuroBarley: control of leaf diseases in barley across Europe - Matzen, N; Weigand, S; Bataille, C; Kildea, S; Havis, N; O’ Driscoll, A; Waite, K; Jalli, Marja; Rodemann, B; Jørgensen, LN (Springer Science and Business Media LLC, 2024)
Barley crops are at risk of being attacked by several leaf diseases. Net blotch, brown rust, Rhynchosporium and Ramularia leaf spot are among the most widespread and can cause severe attack and yield losses. Two trial protocols targeting Ramularia and net blotch, respectively, have been tested in several countries in 2021 and 2022. Ramularia trials were situated in Germany, Ireland, Scotland, and Denmark. The net blotch trials were placed in Denmark, Belgium, the UK, Germany, Finland, and France. In the two protocols, 12–13 different fungicide solutions including co-formulations of DMIs, SDHIs, QoIs, and multi-site inhibitors have been tested to compare efficacy and yield responses. Against Ramularia leaf spot, the fungicides were applied at GS 47–51 and against net blotch at GS 37–45. In six trials, the efficacy against Ramularia leaf spot was scored. The results showed a superior control from the co-formulation fluxapyroxad + metyltetraprole (78–100% control), but also solo mefentrifluconazole and the mixtures fluxapyroxad + mefentrifluconazole performed well (average 74–76% control). The mixture fluxapyroxad + metyltetraprole provided the best yield increase followed by Ascra Xpro. Folpet as a solo solution was inferior. Following the net blotch protocol, only three trials developed enough disease to rank the different fungicides; however, in five trials ranking against brown rust was also possible. Most treatments gave very good control of net blotch, and brown rust (> 80% control). The mixture fluxapyroxad + metyltetraprole delivered the best control against all diseases overall. Average yield responses from eight trials showed very similar increases from the tested fungicides.
Keywords: kasvinsuojelu; ipm; Ramularia collo-cygni; Pyrenophora teres; Puccinia hordei; Fungicides; Field efects; Yield response